The effect of sodium hydroxide on drag reduction using a biopolymer. - Singh, H.K.A.G. (EDP Sciences, 2014)
Drag reduction is observed as reduced frictional pressure losses under turbulent flow conditions and hence, substantially increases the flowrate of the fluid. Practical application includes water flooding system, pipeline transport and drainage system. Drag reduction agent, such as polymers, can be introduced to increase the flowrate of water flowing, reducing the water accumulation in the system and subsequently lesser possibility of heavy flooding. Currently used polymer as drag reduction agents is carboxymethylcellulose, to name one. This is a synthetic polymer which will seep into the ground and further harm our environment in excessive use of accumulation. A more environmentally-friendly drag reduction agent, such as the polymer derived from natural sources or biopolymer, is then required for such purpose. As opposed to the synthetic polymers, the potential of biopolymers as drag reduction agents, especially those derived from a local plant source, are not extensively explored. The drag reduction of a polymer produced from a local plant source within the turbulent regime will be explored and assessed in this study using a rheometer where a reduced a torque produced can be perceived as a reduction of drag. The cellulose powder was converted to carboxymethylcellulose (CMC) by etherification process using sodium monochloroacetate and sodium hydroxide. The carboxymethylation reaction then was optimized against concentration of NaOH. The research is structured to focus on producing the biopolymer and also assess the drag reduction ability of the biopolymer produced against concentration of sodium hydroxide. Â© 2014 Owned by the authors, published by EDP Sciences.